Exploring 'risk' and self-management in relation to chronic joint pain (2013)
Chronic joint pain, specifically knee pain, is a prevalent disabling chronic condition. Policy and clinical guidelines promote education of risk factors and supported self-management to ameliorate predicted demands upon state, society and the individual. Extant literature offers little insight into if and how 'risk' is understood in relation to chronic joint pain. The broad research questions in this thesis ask: do people have knowledge of risk factors for joint pain? How do people conceptualise or experience risk in relation to joint pain? How does risk relate to self-management? Qualitative methodology is used within this study. An interpretive approach is used to explore and understand participants sense making and experiences in relation to the concept of risk. Fifteen participants took part in two in-depth interviews spaced six months apart. Eight of the participants also took part in a diary study between the interviews. Findings reveal that lay explanations about jOint pain, lived experiences of illness, meaning making about the body and subsequent learned strategies to deal with joint pain mirror clinical perspectives of 'risk'. People with joint pain encounter 'risk' as a threat to biography or as hazardous scenarios related to their social environment. Self-management of symptoms is mediated by subjective and socio-contextual factors relating to embodied experiences of pain and lay sense making about how physiology interacts with motion and weight loss. Self-management in relation to 'risk' is about managing threats to self, obligations to others, and hazardous scenarios as well as symptom control. New insights for understanding risk are suggested, taking into account the epistemological, ontological and material elements of people's lives with chronic joint pain.
Indefinite embargo on e-access. For access to the hard copy thesis, check the University Library catalogue.
Keywords: R Medicine; R1 Medicine (General)